PENGARUH TEMPERATUR PEREBUSAN JERAMI TERHADAP SIFAT FISIS MEKANIS PAPAN PARTIKEL - M. I. Iskandar (Universitas Nusa Bangsa, 2014)
Effect of Temperature of Straw Boiling on Mechanical and Physical Properties of Particle BoardÂ Â Â Â Â Â Â Â Â Levels of extractive substances in the straw as much as 10-15% and 12-18% silica content respectively. Two of these substances can inhibit good adhesion bonding between the particles during the sealing process. Treatment of straw boilingÂ before gluing process can reduce the negative effects of extractive substances to the bonding adhesive. The purpose of this study was to determine the effect of temperature of the boiling straw on mechanical and physical properties of particle board. The tested physical properties included density, moisture content, thickness swelling and water absorption while the mechanical properties tested included flexural modulus, fracture modulus, internal bonding strength and screw holding strength. Analysisof statistic of the data used was Complete Random Design (RAL). The treatment consisted of a five-level with three replications so that the total number of trials was fifteen. To determine the effect of treatment carried out the Analysis of Variance. To determine the effect of treatment was significantly different would do a further test the Duncan's multiple range test. Processing data using SAS software, version 6123. The results showed an increase in the temperature of straw boiling was very significant and fluctuative on the properties of particle board and the moisture content, thickness swelling 24 hours, flexural modulus (MOE), fracture modulus (MOR), but did not significant affect the density and internal bonding strength. Boiling temperature 40â°C on straw produce panels with the best qualities. The properties of particle board research results that met the requirements of Standard JIS A 5908: 215 only the density and moisture content.Keywords: temperature, boiling, straw, mechanical physical propertiesÂ ABSTRAKÂ Â Â Â Â Â Â Â Kadar zat ekstraktif dalam jerami sebanyak 10-15% dan kadar silika 12-18%. Dua zat tersebut dapat menghambat ikatan rekat yang baik antar partikel pada waktu proses perekatan. Perlakuan perebusan jerami sebelum proses perekatan dapat mengurangi pengaruh negatif zat ekstraktif terhadap ikatan rekat. Tujuan penelitian ini adalah untuk mengetahui pengaruh temperatur perebusan jerami terhadap sifat fisis mekanis papan partikel. Sifat fisis yang diuji meliputi kerapatan, kadar air, pengembangan tebal dan daya serap air sedangkan sifat mekanis yang diuji meliputi modulus lentur, modulus patah, keteguhan rekat internal dan kuat pegang sekrup. Analisis statistik data yang digunakan adalah Rancangan Acak Lengkap (RAL). Perlakuan terdiri dari lima taraf dengan ulangan sebanyak tiga sehingga jumlah total percobaan adalah lima belas. Untuk mengetahui pengaruh dari perlakuan dilakukan analisis ragam (Analysis of Variance). Untuk mengetahui pengaruh berbeda nyata perlakuan dilakukan uji lanjut dengan uji wilayah berganda Duncan. Pengolahan data menggunakan software SAS versi 6.123. Hasil penelitian menunjukkan peningkatan temperatur perebusan jerami berpengaruh sangat nyata dan fluktuatif terhadap sifat-sifat papan partikel dan kadar air, pengembangan tebal 24 jam, modulus lentur (MOE), modulus patah (MOR), tetapi tidak berpengaruh nyata terhadap kerapatan dan keteguhan rekat internal. Perebusan jerami pada suhu 40â°C menghasilkan panil dengan sifat-sifat terbaik. Sifat-sifat papan partikel hasil penelitian yang memenuhi persyaratan Standar JIS A 5908:215 hanya kerapatan dan kadar air.Kata kunci: temperatur, perebusan, jerami, sifat fisis dan mekanis